Tranexamic acid for hyperacute primary IntraCerebral Haemorrhage (TICH-2): an international randomised, placebo-controlled, phase 3 superiority trial - Sprigg, Nikola; Flaherty, Katie; Appleton, Jason P.; Al-Shahi Salman, Rustam; Bereczki, Daniel; Beridze, M.; Christensen, Hanne; Ciccone, Alfonso; Collins, Ronan; Czlonkowska, Anna; Dineen, Robert A.; Duley, Lelia; et al. (Elsevier, 2018)
Background Tranexamic acid (TXA) reduces death due to bleeding after trauma and post-partum haemorrhage. The aim was to assess if tranexamic acid reduces haematoma expansion and improves outcome in adults with stroke due to intracerebral 6 haemorrhage (ICH). Methods We undertook an international, randomised placebo-controlled trial in adults with intracerebral haemorrhage. Participants received 1g intravenous tranexamic acid bolus followed by an 8 hour 1g infusion, or matching placebo, within 8 hours of symptom onset. The primary outcome was functional status at day 90, measured by shift in the modified Rankin Scale (mRS), using ordinal logistic regression, with adjustment for stratification and minimisation criteria. All analyses were performed on an intention to treat basis. This trial is registered as ISRCTN93732214. Findings We recruited 2,325 participants (TXA 1161, placebo 1164) from 124 hospitals in 12 countries between 2013 and 2017. Treatment groups were well balanced at baseline. The primary outcome was determined for 2307 (99·2%) participants. There was no statistically significant difference between the groups for the primary outcome of functional status at day 90 (adjusted odds ratio [aOR] 0·88, 95% CI 0·76-1·03, p=0·11). Although there were fewer deaths by day 7 in the TXA group (aOR 0·73, 95% CI 0·53-0·99, p=0·0406), there was no difference in case fatality at 90 days (adjusted hazard ratio 0·92, 95% CI 0·77 to 1·10, p =0·37). There were fewer serious adverse events after TXA vs. placebo by days 2 (p=0·0272), 7 (p=0·0200) and 90 (p=0·0393). Interpretation There was no significant difference in functional status 90 days after intracerebral haemorrhage with tranexamic acid, despite a reduction in early deaths and serious adverse events. Larger randomised trials are needed to confirm or refute a clinically significant treatment effect.